Identifikasi Metabolit Sekunder Ekstrak Etil Asetat Biji Alpukat (Persea americana Mill.) dan Uji Toksisitas Terhadap Larva Udang Artemia salina Leach. - Musyarrifah, Musyarrifah; Ilyas, Asriani; Baharuddin, Maswati (Al-Kimia, 2014)
Since ancient times the people of Indonesia have known, and using nutritious plant as one of the efforts in the prevention of health problems. Plants belonging to the family Lauraceae is one of a group of plants commonly used by communities as traditional medicine, one of which is Avocado (Persea americana Mill.) Especially in the seeds, which contain secondary metabolites, namely polyphenols, tannins, flavonoids, triterpenoids, quinone, monoterpenoid and seskuiterpenoid and saponins. This study aims to identify the secondary metabolites contained in the seeds of avocado (Persea americana Mill.) And determine the toxicity of extracts and pure compounds using Brine Shrimp Lethality Test (BSLT). Avocado seed solvent extracted using ethyl acetate and the extract obtained was tested group and toxicity testing. The results showed that the ethyl acetate extract of avocado seeds contain phytochemicals based on test results of secondary metabolites, the flavonoids, alkaloids and steroids. Avocado seed solvent extracted using ethyl acetate and the extract obtained was tested group and toxicity testing. The results showed that the ethyl acetate extract of avocado seeds contain phytochemicals based on test results of secondary metabolites, the flavonoids, alkaloids and steroids.